Pengaruh Literasi Keuangan dan Dampak Pinjaman Online terhadap Gaya Hidup Konsumtif bagi Pekerja SPBU di Bululawang - Denvinta Kiki Dewi Pertiwi; Nur Laili Fikriah (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2026)
The rapid development of financial technology, particularly online lending, has transformed consumption patterns among working-age individuals by providing easy access to digital credit. This study aims to analyze the influence of financial literacy and online loans on the consumptive lifestyles of gas station workers in the Bululawang area. An explanatory quantitative approach was employed, with all gas station workers serving as the study population. A saturated sampling (census) technique was applied, and data were collected through digital Likert-scale questionnaires. The hypotheses were tested using Multiple Linear Regression Analysis. The findings indicate that financial literacy does not significantly reduce consumptive lifestyles, suggesting that financial knowledge alone is insufficient to control spending behavior without strong self-discipline. In contrast, the use of online loan applications has a significant positive effect on consumptive behavior, as rapid access to credit creates a perception of greater purchasing power and encourages impulsive spending to satisfy lifestyle and social prestige. Simultaneously, limited financial literacy combined with easy access to digital credit significantly increases consumptive lifestyles. The study concludes that improving financial management requires not only theoretical financial literacy but also practical financial discipline. Therefore, companies are encouraged to provide continuous financial education and develop safer internal financing alternatives to reduce workers' dependence on digital lending platforms.